Modification of a low-cost potentiostat for its use in the synthesis and verification of the pseudocapacitance of the MnO2 - Rojas-Bolaños, Omar (2025)
In this work, several modifications to the circuit of a previously-presented low-cost potentiostat are proposed, and new software is created using the Arduino Integrated Development Environment (IDE). These changes are introduced to reduce the dependency of licensed software and to improve the accuracy of the measurements in tests that require higher currents than those reported in the original paper. During evaluation, the modified potentiostat shows better performance than the original version and its results are similar to those obtained with a professional equipment. In the verification of Ohm’s Law, the modified equipment can estimate the values of the underlying resistors with an error lower than 1%. During the MnO2 electrodeposition, the equipment reaches current values close to 5mA and the rectangular shape of the cyclic voltammograms of the produced MnO2 films are consistent with the previously reported pseudocapacitive properties of MnO2. These results support the use of instruments based on open-source platforms in teaching and research activities.